New Typical Vector of Neurotoxin β-N-Methylamino-l-Alanine (BMAA) in the Marine Benthic Ecosystem - Aifeng Li; Jialiang Song; Yang Hu; Longji Deng; Ling Ding; Meihui Li (Marine Drugs, 2016)
The neurotoxin β-N-methylamino-l-alanine (BMAA) has been identified as an environmental factor triggering neurodegenerative diseases such as Amyotrophic Lateral Sclerosis (ALS) and Alzheimer’s disease (AD). We investigated the possible vectors of BMAA and its isomers 2,4-diaminobutyric acid (DAB) and N-2(aminoethyl)glycine (AEG) in marine mollusks collected from the Chinese coast. Sixty-eight samples of marine mollusks were collected along the Chinese coast in 2016, and were analyzed by an HILIC-MS/MS (hydrophilic interaction liquid chromatography with tandem quadrupole mass spectrometer) method without derivatization. BMAA was detected in a total of five samples from three species: Neverita didyma, Solen strictus, and Mytilus coruscus. The top three concentrations of free-form BMAA (0.99~3.97 μg·g−1 wet weight) were detected in N. didyma. DAB was universally detected in most of the mollusk samples (53/68) with no species-specific or regional differences (0.051~2.65 μg·g−1 wet weight). No AEG was detected in any mollusk samples tested here. The results indicate that the gastropod N. didyma might be an important vector of the neurotoxin BMAA in the Chinese marine ecosystem. The neurotoxin DAB was universally present in marine bivalve and gastropod mollusks. Since N. didyma is consumed by humans, we suggest that the origin and risk of BMAA and DAB toxins in the marine ecosystem should be further investigated in the future.